Food aid and child nutrition in rural Ethiopia - Quisumbing, Agnes R. (International Food Policy Research Institute, 2003)
Food aid programs have become increasingly important for disaster relief in many developing countries. In Ethiopia, a drought-stricken economy with one of the lowest per capita incomes in the world, food aid has amounted to almost 10 million metric tons (mt) from 1984 to 1998, almost 10 percent of annual cereal production. Because of the importance of food aid in Ethiopia, much effort has been devoted to evaluation of its effectiveness.....Many evaluations of food aid have examined its impact on household calorie availability. This paper focuses on the effects of food aid on individual nutritional status, as measured by indicators of child nutrition. -- from Author's Abstract